Gambaran Program Bimbingan Pribadi dan Sosial untuk Meningkatkan Penyesuaian Sosial Siswa - Harahap, Ade Chita Putri; Siregar, Dewi Kumala Kholisa; Husna, Natasya; Putri, Maulida Amelia; Batubara, Muhammad Alwi; Ritonga, Rizki Rahmayani; Supriyadi, Supriyadi; Ramadhita, Zahrani (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The goal of this study is to gain an overview of personal and social guidance programs that can help students better adjust to social situations in the classroom. The description of the guiding program was discovered using qualitative research techniques. Interviews were the primary data gathering method employed in this study. In this study, counseling professors from MA Mualimin UNIVA in Medan City served as interview subjects. As a result, group and individual counseling are the techniques employed in personal and social therapy to enhance students' social adjustment. Effective communication techniques, the capacity to control one's emotions, the development of confidence, the management of stress, and an understanding of the significance of preserving one's mental and physical health are among the topics covered in the guiding program. However, social scientists and academics also discovered challenges in the implementation of personal guidance programs, including a lack of parental support, time restraints, and limited resources. It is crucial to do study on initiatives aimed at enhancing students' social adjustment. Previous research has demonstrated that group guidance programs can aid pupils in enhancing their social adjustment. Students can learn to identify and handle personal or social issues that affect their capacity to adapt to their surroundings through a successful personal and social counseling program. Keywords: Guidance and Counseling, Personal and social guidance, Students' social adjustment